British Red Squirrels Remain the Only Known Wild Rodent Host for Leprosy Bacilli - Schilling, Anna-Katarina; Avanzi, Charlotte; Ulrich, Rainer G.; Busso, Philippe; Pisanu, Benoit; Ferrari, Nicola; Romeo, Claudia; Mazzamuto, Maria Vittoria; McLuckie, Joyce; Shuttleworth, Craig M.; Del-Pozo, Jorge; Lurz, Peter W. W.; et al. (Frontiers in Veterinary Science, 2019)
Eurasian red squirrels (Sciurus vulgaris) in the British Isles are the most recently discovered animal reservoir for the leprosy bacteria Mycobacterium leprae and Mycobacterium lepromatosis. Initial data suggest that prevalence of leprosy infection is variable and often low in different squirrel populations. Nothing is known about the presence of leprosy bacilli in other wild squirrel species despite two others (Siberian chipmunk [Tamias sibiricus], and Thirteen-lined ground squirrel [Ictidomys tridecemlineatus]) having been reported to be susceptible to experimental infection with M. leprae. Rats, a food-source in some countries where human leprosy occurs, have been suggested as potential reservoirs for leprosy bacilli, but no evidence supporting this hypothesis is currently available. We screened 301 squirrel samples covering four species (96 Eurasian red squirrels, 67 Eastern grey squirrels (Sciurus carolinensis), 35 Siberian chipmunks, and 103 Pallas’s squirrels (Callosciurus erythraeus)) from Europe and 72 Mexican white-throated woodrats (Neotoma albigula) for the presence of M. leprae and M. lepromatosis using validated PCR protocols. No DNA from leprosy bacilli was detected in any of the samples tested. Given our sample-size, the pathogen should have been detected if the prevalence and/or bacillary load in the populations investigated were similar to those found for British red squirrels.